2000
DOI: 10.1246/bcsj.73.215
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ladder and Cage Silsesquioxanes from 1,2,3,4-Tetrahydroxycyclotetrasiloxane

Abstract: The versatility of cis,cis,cis-1,3,5,7-tetrahydroxy-1,3,5,7-tetraisopropylcyclotetrasiloxane (1) as a precursor of cage and ladder siloxanes is presented. Compound 1 reacted with 1,3-dichloro-1,1,3,3-tetraisopropyldisiloxane in pyridine to give 1,3,5,5,7,7,9,11,13,13,15,15-cis-cisoid-cis-dodecaisopropyltricyclo[9.5.1.13,9]octasiloxane (2) in 20% yield. The reaction proceeded with retention of the configuration of the silicon atoms, and only syn-type isomer was obtained. The reaction of 1 with 1,1,3,3-tetrachlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 11 publications
1
69
0
Order By: Relevance
“…Polycondensation of all-cis or cis-trans-cis isomers of cyclic tetrasilanols [13] or isocyanates [14] gives linear polymers of high regularity and defined tacticity. Unno et al reported the stepwise stereo-controlled condensation of cyclosilanols for the preparation of tricyclic [15] pentacyclic [16] bi-, tri-, tetra-and pentacyclic ladder siloxanes with an all-anti conformation [17], nonacyclic [18] as well as heptacyclic ladder siloxanes and methyl-substituted ladder polysilsesquioxanes [19]. Ladder oligosilsesquioxanes of low molecular weight were also prepared by controlled condensation of an isocyanate functionalized cyclosiloxane precursor: cis,trans,cis-[MeSi(NCO)O] 4 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Polycondensation of all-cis or cis-trans-cis isomers of cyclic tetrasilanols [13] or isocyanates [14] gives linear polymers of high regularity and defined tacticity. Unno et al reported the stepwise stereo-controlled condensation of cyclosilanols for the preparation of tricyclic [15] pentacyclic [16] bi-, tri-, tetra-and pentacyclic ladder siloxanes with an all-anti conformation [17], nonacyclic [18] as well as heptacyclic ladder siloxanes and methyl-substituted ladder polysilsesquioxanes [19]. Ladder oligosilsesquioxanes of low molecular weight were also prepared by controlled condensation of an isocyanate functionalized cyclosiloxane precursor: cis,trans,cis-[MeSi(NCO)O] 4 [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The variation of the Si-O bond lengths covers a narrow range between 1.627 Å and 1.643 Å which is smaller than in the other structure reports where variations as much as 0.04 to 0.28 Å are reported. Until now, only a few structure determinations of hexa(alkyl/aryl)silsesquioxanes with this Si6O9 cage can be found in the literature including tert-butyl [16], cyclohexyl [23], 1,1,2-trimethylpropyl [24], 2,4,6-triisopropylphenyl [25], trimethoxysilyl [26], and isopropyl [27] substituted hexasilsesquioxanes. For these, the mean value of the Si-O-Si angles in the six-membered rings is 130.2(4)°, the mean value of the other Si-O-Si angles is 140.0(8)° (min.…”
Section: Resultsmentioning
confidence: 99%
“…However, synthesis of ladder was not achieved on industry stage because conventional synthesis methods were not suitable for mass-production with multi-step process and low yield. [4][5][6] Moreover, the film properties of ladder structure SQ had not been enough announced until today. Here we proposed new synthesis method for oligo-ladder phenyl silsesquioxane (LPSQ).…”
Section: Fig1 Ladder-structure With Cis-syndiotactic Configurationmentioning
confidence: 99%
“…It is obtained by an aqueous-organic liquid boundary reaction via silicon-pyridine interaction compound. Our synthesis method is one-pot reaction, which is simple and generates a high yield rather than previous reports [3][4][5][6] The film derived from SQ has been studied for a long times, however they still keep our interest due to large expectation from their unique characteristic. In recent years, practical applications for semi-conductor interlayer dielectrics, photo-resist material and flat panel display industry have been proposed as LPSQ application.…”
Section: Fig1 Ladder-structure With Cis-syndiotactic Configurationmentioning
confidence: 99%